The responses of three dominant species to increased rainfall under different grazing systems in a desert steppe. Issue 6 (29th June 2022) - Song, Yifan; Liu, Tiejun; Wang, Jing; Lu, Yajing; Guo, Jianying; Dong, Zhi; Wen, Yunhao; Pei, Zhiyong
Abstract: Compared with drought stress, our knowledge about the potential precipitation increase in desert steppes and its ecological effects is still limited. In order to improve our understanding of the responses of desert steppe plants to climate change and human activities, we performed a 3‐year‐long controlled water addition experiment in grasslands with different grazing systems. The results showed that increased water changed the plant height/above‐ground biomass/leaf‐tissue thickness of Stipa breviflora Griseb., Cleistogenes squarrosa (Trin.) Keng and Convolvulus ammannii Desr. by +23.86%/+77.35%/−19.09%, +14.67%/+162.34%/−16.62% and + 29.14%/+69.37%/−22.85%, respectively, compared to those in the control group. The net photosynthetic rate, stomatal conductance, transpiration rate and water‐use efficiencies of these three types of plants increased by 0.32%–43.71% with water addition, compared to the corresponding parameters in the control group. We also found that plant responses to increased rainfall were not always positive. Under the unique environmental conditions of desert steppes, increase in rainfall has a limited restorative effect on vegetation and an excessive increase in rainfall may actually inhibit plant growth and exacerbate grazing grassland degradation. Compared to rotational grazing and continuous grazing grasslands, plants in enclosed grasslands had higher restoration thresholds and better restorative effect following increased rainfall. Enclosure increased the adaptability and resilience of grazing grassland plants towards increased rainfall. Under the background of increased rainfall, while we look forward to the ecological restoration in desert steppe, we also need to be alert to the potential adverse effects of excessive rainfall on grazing grasslands. Abstract : The adaptation of the three dominant species to increased rainfall would manifest as increased plant height and above‐ground biomass, decreased leaf‐tissue thickness, improved photosynthetic capacity and enhanced water‐use efficiency. In ecologically fragile desert steppes, an increase in rainfall is beneficial for ecological restoration as a whole, but not always. As compared to the grazing grasslands, the vegetation in the enclosed grasslands had a higher restoration threshold and a greater range of adaptability with respect to increased rainfall.